Study of development of agro-tourism potential on tea small-holder - Trimo, Lucyana; Nurafifah, Iis (Research Institute for Tea and Cinchona, 2017)
Tea Small-Holder can be managed as an agro-tourism destination which becomes a very popular tourist destination in the present and future, domestically and also for foreigners; that can support Government in providing jobs in the rural area; develop the countries itself; increase regional income and rural communities, and also support the environment conservation. The objective of this research is to describe agro-tourism potential of Tea Small-Holder at Desa Pulosari, Kecamatan Pangalengan Kabupaten Bandung, and search the potential products to be developed as a main tourism object. Case study method was used in this research, whereas the informants were appointed purposely and data were analyzed by triangulating method. Several potentials of tea plantation which can be used as an agro-tourism of Kelompok Tani Neglasari and people surrounding Desa Pulosari, Kecamatan Pangalengan are as follows: a) the main facilities are already available and adequate enough and objects of tourism such as tea plantation and tourist attractions such as art and culture e.g. Singa Depok, Pencak Silat and harvest ritual; b) supplementary facilities such as culinary and lodging facilities which provided by local villagers. Tourism products which can be offered by the locals to the tourists are: Package I: lodging facility and tour of nature, culinary, knowledge (e.g. tea commodities), and culture (harvest ritual);Â Package II: lodging facility and tour of nature, culinary, knowledge about tea, and in addition there are other supporting activities, e.g. tour of knowledge related to coffee and horticulture; culture, e.g. as Singa Depok performance; Package III : Package II equipped with knowledge of farm animals e.g. livestock dairy cattle, and tour of culture, e.g. harvest ritual, Singa Depok and Pencak Silat.